Microsoft Azure SQL Data Warehouse - Architecture and SQL - Tom Coffing, Todd Wilson (Tera-Tom genius series, 2015)
One of the most popular databases worldwide is Microsoft's SQL Server. Now Microsoft has introduced their MPP data warehouse system, designed for the cloud, called the Microsoft Azure SQL Data Warehouse. The Microsoft Azure Cloud is rapidly making T-SQL one of the standards of SQL among millions of companies. This book details the architecture of the Azure SQL Data Warehouse and the SQL commands available. This book is perfect for anyone who works with the Microsoft Azure SQL Data Warehouse. This book educates readers on how to create tables and indexes, how the data is distributed, and how the system process the data. Plus, it is followed up with over 700 pages of SQL examples and explanations. This book is a must have for anyone designing, implementing or querying the system. The Authors of Tera-Tom Coffing, who has written over 70 successful books and Todd Wilson, CTO of Coffing Data Warehousing bring a combination of minds together made up of experience and real business world knowledge.